Analysis of SPMI Implementation at SMPS Muhammadiyah Plus Bengkalis and its Impact on Teachers' Professional Competence: Analisis Implementasi SPMI di SMPS Muhammadiyah Plus Bengkalis dan Dampaknya Terhadap Kompetensi Profesional Guru - Syafriadi; Nurdyansyah (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality education requires structured frameworks to ensure sustainable academic standards across educational institutions. Specific Background: Internal quality assurance systems guide school governance, lesson planning, and instructional execution. Knowledge Gap: However, field execution often lacks alignment between administrative standards and practical teacher professional competence development. Aims: This study analyzes the implementation of the internal quality assurance system at SMPS Muhammadiyah Plus Bengkalis and evaluates its contribution to teacher professional competence. Results: Qualitative findings indicate positive growth in lesson planning, classroom management, and technology-based learning integration, although limited pedagogical supervision and resource constraints remain active challenges. Novelty: This research highlights quality assurance dynamics within a faith-based private junior high school context in a specific local region. Implications: Systematic teacher training, effective pedagogical supervision, and data-driven evaluation tools are necessary to foster sustainable educational quality culture. Key Findings Highlights Implementation of internal quality assurance improves lesson planning, classroom execution, and digital media integration. Administrative supervision and limited facilities hinder optimal pedagogical skill development. Continuous training and structured monitoring are essential to establish an effective school quality culture. Keywords: Internal Quality Assurance System, Teacher Professional Competence, Educational Quality, Pedagogical Supervision, Continuous Improvement